Testing Bergmann's rule in marine copepods. Issue 9 (10th August 2021) - Campbell, Max D.; Schoeman, David S.; Venables, William; Abu‐Alhaija, Rana; Batten, Sonia D.; Chiba, Sanae; Coman, Frank; Davies, Claire H.; Edwards, Martin; Eriksen, Ruth S.; Everett, Jason D.; Fukai, Yutaka; et al.
Abstract : Macroecological relationships provide insights into rules that govern ecological systems. Bergmann's rule posits that members of the same clade are larger at colder temperatures. Whether temperature drives this relationship is debated because several other potential drivers covary with temperature. We conducted a near‐global comparative analysis on marine copepods (97 830 samples, 388 taxa) to test Bergmann's rule, considering other potential drivers. Supporting Bergmann's rule, we found temperature better predicted size than did latitude or oxygen, with body size decreasing by 43.9% across the temperature range (‐1.7 to 30ºC). Body size also decreased by 26.9% across the range in food availability. Our results provide strong support for Bergman's rule in copepods, but emphasises the importance of other drivers in modifying this pattern. As the world warms, smaller copepod species are likely to emerge as 'winners', potentially reducing rates of fisheries production and carbon sequestration.